PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL PEMBELAJARAN BIOLOGI KELAS X SMAN 2 KOTO BARU KABUPATEN DHARMASRAYA - Kamala, Mutia - (Pendidikan Biologi, 2014)
The background of this research is about the low of learning biology outcomes at X class students in SMAN 2 Koto Baru. Students low of learning biology outcomes are caused by several factors including the learning unattractive and boring. Teachers tend to use conventional method and don not use the learning model of TSTS yet. The aim of this study is to examine the effect of the application of cooperative learning model with two stay two stray towards learning biology outcomes. The type of this research is experimental research with randomized control group post-test only design. The population is all the student at X class in SMAN 2 Koto Baru Dharmasraya academic year 2013/2014. The sampling technique is purposive sampling. The instrument is the ultimate test of learning outcomes in the form of an objective test. Based on the result of the research, it obtains the average learning outcomes in experimental class and control class is 70.92 63.22. It can be concluded that this model influence on student learning outcomes.